Does the Glass Ceiling Exist? : A Cross-National Perspective on Gender Income Mobility - Ira N. Gang; John S. Landon-Lane; Myeong-Su Yun (Rutgers University, Department of Economics, 2003)
We compare male and female upward labor income mobility in Germany and the United States using the GSOEP-PSID Cross-National Equivalent File. Our main interest is to test whether a glass ceiling exists for women. Conventional thinking about the glass ceiling highlights the belief that the playing field is level for women and men in the labor market up to a certain point, after which there is an effective limit on advancement for women. We examine the glass ceiling hypothesis by looking at the income dynamics ? the movement of women and men through the distribution of income over time. We find that there is considerable evidence in favor of a glass ceiling both in Germany and the United States with men having approximately a 30% premium in their upward income mobility compared to women in the upper income classes. We also find significant, but smaller, differences at middle and low income levels for both countries.
Keywords: D3; D63; J7; 330; glass ceiling; mobility; Markov chain; income distribution dynamics; gender discrimination; Frauenarbeitslohn; Erwerbsverlauf; Lohndifferenzierung; Soziale Mobilität; Geschlecht; Schätzung; Vereinigte Staaten; Deutschland